서울시내 일부 저소득층 학동기 아동의 신체발달 및 식습관 - 남경희(Kyung-Hui Nam); 김영미(Young-Mee Kim); 이고은(Go-Eun Lee); 이유나(Yu-Na Lee); 정효지(Hyojee Joung) (Korean journal of community nutrition, 2006)
Since the economic crisis in 1997, the number of low income families has increased and the turmoil is likely to affect nutritional and health status of the children in low-income families. The purpose of this study was to investigate dietary behaviors and physical development of low income family children in the Seoul area. The subjects were 44 boys and 56 girls, between the ages of 7 and 12 years, from the beneficiary families of the governmental assistant program and enrolled in after school-care centers. A self-reported questionnaire, including general characteristics and dietary behaviors, was applied to the children and their parents. Skipping meal rate was higher in breakfast than in lunch or dinner, and was less frequent in parents and children families compared to that of the other types of families (p<0.05). Most students are shown that they usually keep the dietary guideline for Korean children. There were significant differences in keeping the dietary guidelines between the parents and children family group and other groups in several items. The results imply that the nutrition education program should be more focused on the families which are not composed of parents and children.